Ipv4 Lan Mapping Using Vlsm At Pt Bimasakti Mandiri Perkasa Indonesia - Aziz Setyawan Hidayat; Felix Wuryo Handono; Sumarna (Jurnal Mantik, 2022)
The selection of the topology used is based on devices that have a non-stop work rate with network devices that have a low level of work being a method of grouping within the network topology. The company has 500 employees and consists of 17 branch offices and 1 head office, while the IP addresses used on all network devices use IPv4 using class B, which is 172.16.0.0 with a subnet mask of /24 or 255.255.255. With the use of class B subnet blocks 172.16.0.0/24, 18 subnet blocks are needed, namely subnet blocks 172.16.0.0/24 to 172.16.17.0/24 because PT Bimasakti Mandiri Perkasa has 1 head office and 17 branch offices. spread throughout Indonesia. Furthermore, when viewed from the side of the use of IP addresses, many IP addresses are not used because they equally divide the provision of addresses at the 18 company offices as many as 254 IP addresses, while the use of IP addresses in each office is different. To make efficient use of IP addresses that will be applied to computer networks, a good method is to use VLSM.